The influence of targeted therapies in the inner ear - Bonilla, Tony; DiFatta, Jake; Bas Infante, Esperanza; Goncalves, Stefania (Frontiers in Pharmacology, 2025)
Scientific research has significantly propelled advancements in healthcare. One notable application is precision medicine, which seeks to analyze and comprehend disease pathology to offer personalized medical treatments to patients. Targeted oncology, a branch of precision medicine, focuses on identifying and targeting specific molecules that regulate cancer cells, thereby minimizing harm to healthy cells. Different types of targeted therapy against cancer include monoclonal antibodies and small molecules. This manuscript intends to provide an overview of the influence of these targeted oncology and non-oncology therapies on hearing. Furthermore, side effects including immune-related adverse events will be reviewed as potential causes of hearing deterioration in this patient population.